O Teatro Mágico e suas perspectivas sociais em uma visão bakhtiniana - Fernandes, Melissa de Figueiredo Silva (2020)
Teatro Mágico is a musical group that was created in 2003 by musician, composer and instrumentalist Fernando Anitelli. The troupe, as the group is also known, was inspired by soirees and brings together various artistic expressions, such as dance, circus, acrobatic performances, poetry and literature. It brought to the stage the experiences shared in meetings with several artists who believed in art as a way of manifesting ideas. The project, taking into account the redirection of the public's relationship with music, incorporated the idea of free music and, consequently, the creation of the acronym MPB (downloadable music). This work analyzes three song lyrics from the musical group O Teatro Mágico, which were selected due to their comparison with the totality of their work, presenting characteristics of the group in dialogue with the political and social fields of Brazil in recent decades. The main objective of this research is to find out how the lyrics of Teatro Mágico's music establish dialogical relations with the country's social, political and economic scenario, based on concepts created by the Russian philosopher Mikhail Bakhtin, since one of the characteristics of the songs is the presence of statements with a critical, ironic and reflective content. To compose the object of research, three songs were chosen, which carry the aforementioned social criticism characteristic: O mérito e o monstro, Este mundo não vale o mundo and O sol e a peneira. For this, Bakhtinian conceptual contributions were listed, such as those of discourse genre, ideology, intertextuality and interdiscursivity and enunciation, categories that are essential for the analysis of the compositions since, for Bakhtin, dialogical relations can be present in a single word, if we take into account that the word itself pervades its existing meaning in the dictionary. The lyrics were analyzed, through a qualitative analysis, making reference to the Bakhtinian theory and concepts, taking into account the historical context of the songs production. Through the analysis of the lyrics of the songs, the importance of art and culture was observed, as a way of producing statements that dialogue with issues of such complexity that are present in our social and political context. Keywords: Teatro Mágico; dialogical relations; song lyrics; Bakhtin.